Linking irrigation development with the wider agrarian context: everyday class politics in water distribution practices in Rural Java - Suhardiman, Diana (Informa UK Limited, 2018)
Poor performance of government managed irrigation systems persists globally despite numerous policies over the last four decades to address the problem. I argue that policy efforts to improve irrigation performance in developing countries fail in part because they are often formulated in isolation from the existing agrarian reality. This article uses the example of Indonesia to show the link between irrigation outcomes and the wider agrarian context and highlights how the interface between farmers and irrigation bureaucracies is shaped by the existing agrarian structure.